Bioactive nanocomposite coatings under visible light illumination promoted surface-mediated gene delivery. (1st June 2020) - Yao, Lili; Wang, Xiaozhao; Weng, Wenjian; Fu, Yongqing; Cheng, Kui
Abstract : Bioactive coatings with photothermal conversion ability were used to spatially and temporally control surface-mediated gene delivery under visible light illumination. Abstract : Gene delivery based on bioactive coatings on collagen has great potential for applications in bone repair. Meanwhile, controlled gene delivery at specific times/regions is essential for an efficient and complete bone reconstruction process. However, spatio-temporal regulation of gene release and delivery remains a great challenge. In this paper, we used visible light illumination to effectively regulate gene release and subsequent delivery into biological cells. A visible light responsive and bioactive nanocomposite coating (based on collagen/gold nanoparticles, e.g., Col/AuNPs) was prepared through hydrothermal and sol–gel processes and was used as a loading platform for complexes of enhanced green fluorescent protein and Lipofectamine2000 (LF/GFP). The results showed that the amount of immobilized LF/GFP was increased on Col/AuNPs and the release of pre-adsorbed LF/GFP was significantly enhanced in a spatio-temporal and controlled manner under visible light illumination. Moreover, the cellular intake of the released genes was improved, thus enhancing the gene expression efficiency of the cells. The mechanism of enhanced controlled gene delivery was attributed to the changes in collagen structures and rearrangement of cytoskeletal structures induced by the photothermal effect. The developed Col/AuNP composite coating is effective for both controlled surface-mediated gene delivery and gene-mediated bone repair.